Involvement of V-ATPase in the regulation of cell size in the fly's visual system. - Pyza, E.; Borycz, J.; Giebultowicz, J.M.; Meinertzhagen, I.A. (Journal of Insect Physiology, 2004)
In the fly's visual system, two classes of lamina interneuron, L1 and L2, cyclically change both their size and shape in a rhythm that is circadian. Several neurotransmitters and the lamina's glial cells are known to be involved in regulating these rhythms. Moreover, vacuolar-type H+-ATPase (V-ATPase) in the optic lobe is thought also to participate in such regulation. We have detected V-ATPase-like immunoreactivity in the heads of both Drosophilla melanogaster and Musca domestica using antibodies raised against either the B- or H-subunits of V-ATPase from D. melanogaster or against the B-subunit from two other insect species Culex quinquefasciatus and Manduca sexta. In the visual systems of both fly species V-ATPase was localized immunocytochemically to the compound eye photoreceptors. In D. melanogaster immunoreactivity oscillated during the day and night and under constant darkness the signal was stronger during the subjective night than the subjective day. In turn, blocking V-ATPase by injecting a V-ATPase blocker, bafilomycin, in M. domestica increased the axon sizes of L1 and L2, but only when bafilomycin was applied during the night. As a result bafilomycin abolished the day/night difference in axon size in L1 and L2, their sizes being similar during the day and night.